SEROPREVALENCE OF TOXOPLASMA GONDII INFECTION AMONG PATIENTS ADMITTED TO AL-ZAHRA HOSPITAL, ISFAHAN, IRAN - Mohaghegh, Mohammad Ali; Yazdani, Hajar; Hadipour, Mahboobe; Namdar, Fatemeh; Azami, Mehdi; Kalani, Hamed; Mirzaei, Farzaneh; Hejazi, Seyed Hossein; Taghavi-Shahri, Seyed Mahmood; Ghomashlooyan, Mohsen (Journal of Ayub Medical College Abbottabad, 2015)
Background: Toxoplasma gondii (T. gondii) infection is one of the most common parasitic infections among humans and other warm-blooded animals worldwide. The aim of this study was to evaluate toxoplasmosis status in patients admitted to Al-Zahra hospital, Isfahan, Iran. Methods: This cross-sectional study was conducted from October 2012 to January 2015. During this period, 716 patients referred to Al-Zahra hospital in Isfahan city, Iran, were studied to investigate the IgG and IgM antibodies against T. gondii using ELISA kit. The data were analysed by Chi-square and Fisher's exact tests. In addition, the relation of data with age and sex were also examined. Results: Among 716 patients, 21 patients (2.9%) had positive IgM and 288 patients (40.2%) had positive IgG titer against T. gondii. Data analysis by Chi-square and Fisher's exact tests revealed that there was no significant relationship between IgG titer and age (p>0.05). Additionally, there was no relationship between IgM titer and age (p>0.05). The data showed that there was no relationship between IgG and IgM antibody titer and sex (p>0.05). Conclusion: The prevalence of toxoplasmosis in Isfahan inhabitants seems fairly high but it can be concluded that the rate of seropositive patient is moderate comparing to other regions of country. Accordingly, the authors propose that all sensitive patients have to be tested for T. gondii antibody in order to prevent the consequences of disease.